S-s-snakes! - Penner, Lucille Recht; Barrett, Peter (New York : Random House, 1994)
Discusses different species of snakes and their characteristics, behavior, and environments.
510
Accelerated Reader AR
Keywords: Snakes -- Juvenile literature; Snakes